Use of Mixed Methods in Emotional/Behavioral Disorders Intervention Research. (May 2023) - Conroy, Maureen; Houchins, David; Hitchcock, John; Anderson, Jeffrey
Increasingly, mixed methods research (MMR) is used in special education, although the extent to which MMR is used in intervention research in the field of emotional/behavioral disorders (EBD) remains unknown. The purpose of this article is to examine the use of MMR in EBD intervention research to describe its application within the field. We conducted a targeted review of two prominent journals to assess the use of MMR over the last 20 years in the field. Following the identification of MMR intervention studies, we applied several frameworks to describe the application of MMR across identified studies. Results of this targeted review indicate that very few EBD intervention studies used MMR. Most studies used singular quantitative approaches (e.g., group experimental or single case research design) and only a small portion used qualitative methods. We did find a number of studies using multimethods by combining two or more quantitative approaches. Our assertion is that researchers consider increasing their use of MMR to advance the science in the field of EBD and to gain a better understanding of the "why" and "how" interventions are or are not effective.